ENT 530 Social Media Portfolio: Ruang Bake / Siti Nordiyana Mohamad Sadzaly - Mohamad Sadzaly, Siti Nordiyana (2021)
Ruang Bake is a dessert shop that specializes in dessert especially the Signature Brownies in Selangor area. The Brownies comes in variety of topping and sizes accordingly to fit each individual customer needs. The price is economical and reasonable which ranging from RM35 to RM67 based on customer requested. Starting from ordering until producing is made by our truly owner. Ruang Bake really particular about the quality and the presentation of the Brownies. Even though the company is handling only by the owner, it’s not a reason to achieve what is desired. Ruang Bake goal is to providing good quality products and aims to offer excellent customer service to each customer that includes fats response on any inquiries within just a few minutes and attending to customer special request such as birthday gift, door gift, specific delivery time and more. This is to ensure that each of their customers are getting the best and delightful shopping experience from the establishment. With this report, I was hoping that by analysing my nature of business and solving a few issues faced by the company would be able to gain a few helpful insights that would give me an opportunity to skyrocket their business into new heights and promote my business in a better way in the future.